Defects in oxygen-depleted titanate nanostructures - Vittadini, Andrea; Schirmer, Michael; Walz, Marie-Madeleine; Vollnhals, Florian; Lukasczyk, Thomas; Steinrück, Hans-Peter; Marbach, Hubertus; Riss, Alexander; Elser, Michael J.; Schürer, Benedikt; Diwald, Oliver (Langmuir, 2012)
The identification of defects and their controlled generation in titanate nanostructures is a key to their successful application in photoelectronic devices. We comprehensively explored the effect of vacuum annealing on morphology and composition of Na Ti O nanowires and protonated H Ti O nanoscrolls using a combination of scanning electron microscopy, Auger and Fourier-transform infrared (FT-IR) spectroscopy, as well as ab initio density functional theory (DFT) calculations. The observation that H Ti O nanoscrolls are more susceptible to electronic reduction and annealing-induced n-type doping than Na Ti O nanowires is attributed to the position of the conduction band minimum. It is close to the vacuum level and, thus, favors the Fermi level-induced compensation of donor states by cation vacancies. In agreement with theoretical predictions that suggest similar formation energies for oxygen and sodium vacancies, we experimentally observed the annealing induced depletion of sodium from the surface of the nanowires. © 2012 American Chemical Society.

Electron-beam-induced deposition and post-treatment processes to locally generate clean titanium oxide nanostructures on Si(100) - Schirmer, Michael; Walz, Marie-Madeleine; Vollnhals, Florian; Lukasczyk, Thomas; Sandmann, Achim; Chen, C.; Steinrück, Hans-Peter; Marbach, Hubertus (Nanotechnology, 2011)
We have investigated the lithographic generation of TiO nanostructures on Si(100) via electron-beam-induced deposition (EBID) of titanium tetraisopropoxide (TTIP) in ultra-high vacuum (UHV) by scanning electron microscopy (SEM) and local Auger electron spectroscopy (AES). In addition, the fabricated nanostructures were also characterized ex situ via atomic force microscopy (AFM) under ambient conditions. In EBID, a highly focused electron beam is used to locally decompose precursor molecules and thereby to generate a deposit. A drawback of this nanofabrication technique is the unintended deposition of material in the vicinity of the impact position of the primary electron beam due to so-called proximity effects. Herein, we present a post-treatment procedure to deplete the unintended deposits by moderate sputtering after the deposition process. Moreover, we were able to observe the formation of pure titanium oxide nanocrystals (>100 nm) in situ upon heating the sample in a well-defined oxygen atmosphere. While the nanocrystal growth for the as-deposited structures also occurs in the surroundings of the irradiated area due to proximity effects, it is limited to the pre-defined regions, if the sample was sputtered before heating the sample under oxygen atmosphere. The described two-step post-treatment procedure after EBID presents a new pathway for the fabrication of clean localized nanostructures. © 2011 IOP Publishing Ltd.

Electron beam induced surface activation of ultrathin porphyrin layers on Ag(111) - Vollnhals, Florian; Wintrich, Patrick; Walz, Marie-Madeleine; Steinrück, Hans-Peter; Marbach, Hubertus (Langmuir, 2013)
We demonstrate how a focused electron beam can be used to chemically activate porphyrin layers on Ag(111) such that they become locally reactive toward the decomposition of iron pentacarbonyl, Fe(CO). This finding considerably expands the scope of electron beam induced surface activation (EBISA) and also has implications for electron beam induced deposition (EBID). The influence of the porphyrin layer thickness on both processes is studied in detail using scanning tunneling microscopy (STM) and scanning electron microscopy (SEM) as well as Auger electron spectroscopy (AES) and scanning Auger microscopy (SAM). While a closed monolayer of porphyrin molecules does exhibit some activity toward Fe(CO) decomposition after electron irradiation, a growth enhancement is found for bi- and multilayer films. This is attributed to a partial quenching of activated centers in the first layer due to the close proximity of the silver substrate. In addition, we demonstrate that the catalytic decomposition of gaseous Fe(CO) on Ag(111) can be effectively inhibited by introducing a densely packed monolayer of 2H-tetraphenylporphyrin (2HTPP) molecules. © 2013 American Chemical Society.

Electron beam-induced writing of nanoscale iron wires on a functional metal oxide - Vollnhals, Florian; Woolcot, Tom; Walz, Marie-Madeleine; Seiler, Steffen; Steinrück, Hans-Peter; Thornton, Geoff; Marbach, Hubertus (Journal of Physical Chemistry C, 2013)
Electron beam-induced surface activation (EBISA) has been used to grow wires of iron on rutile TiO(110)-(1 × 1) in ultrahigh vacuum. The wires have a width down to ∼20 nm and hence have potential utility as interconnects on this dielectric substrate. Wire formation was achieved using an electron beam from a scanning electron microscope to activate the surface, which was subsequently exposed to Fe(CO). On the basis of scanning tunneling microscopy and Auger electron spectroscopy measurements, the activation mechanism involves electron beam-induced surface reduction and restructuring. © 2013 American Chemical Society.

Electrons as "Invisible Ink": Fabrication of nanostructures by local electron beam induced activation of SiOx - Walz, Marie-Madeleine; Schirmer, Michael; Vollnhals, Florian; Lukasczyk, Thomas; Steinrück, Hans-Peter; Marbach, Hubertus (Angewandte Chemie International Edition, 2010)
Figure Presented Beam me up: A novel two-step process allows iron nanostructures to be generated locally on SiO/Si at 300 K. The surface is first locally activated by an electron beam. Then the activated structures are exposed to [Fe(CO)], which decomposes and grows autocatalytically to give pure Fe nanocrystals. © 2010 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.

Fabrication of layered nanostructures by successive electron beam induced deposition with two precursors: Protective capping of metallic iron structures - Schirmer, Michael; Walz, Marie-Madeleine; Papp, Christian; Kronast, F.; Gray, A.X.; Balke, B.; Cramm, S.; Fadley, C.S.; Steinrück, Hans-Peter; Marbach, Hubertus (Nanotechnology, 2011)
We report on the stepwise generation of layered nanostructures via electron beam induced deposition (EBID) using organometallic precursor molecules in ultra-high vacuum (UHV). In a first step a metallic iron line structure was produced using iron pentacarbonyl; in a second step this nanostructure was then locally capped with a 2-3nm thin titanium oxide-containing film fabricated from titanium tetraisopropoxide. The chemical composition of the deposited layers was analyzed by spatially resolved Auger electron spectroscopy. With spatially resolved x-ray absorption spectroscopy at the Fe L edge, it was demonstrated that the thin capping layer prevents the iron structure from oxidation upon exposure to air. © 2011 IOP Publishing Ltd.

Generation of clean iron nanocrystals on an ultra-thin SiO x film on Si(001) - Walz, Marie-Madeleine; Vollnhals, Florian; Schirmer, Michael; Steinrück, Hans-Peter; Marbach, Hubertus (Physical Chemistry Chemical Physics, 2011)
Upon exposure to Fe(CO) , the formation of pure cubic Fe nanocrystals with dimensions up to ∼75 nm is reported on ultra-thin SiO films (thickness ≈ 0.5 nm) on Si(001), which have been prepared in situ under UHV conditions. The active centers for initial decomposition of Fe(CO) resulting in the growth of the Fe clusters are proposed to be SiO sites. After nucleation at these sites, further crystal growth is observed due to autocatalytic dissociation of Fe(CO) at room temperature. The density of the Fe clusters can be increased by irradiating the surface with a focused electron beam (15 keV) prior to gas exposure. The formation of the active SiO sites upon electron irradiation is attributed to oxygen desorption via the Knotek-Feibelman mechanism. © 2011 the Owner Societies.

Investigation of proximity effects in electron microscopy and lithography - Walz, Marie-Madeleine; Vollnhals, Florian; Rietzler, Florian; Schirmer, Michael; Steinrück, Hans-Peter; Marbach, Hubertus (Applied Physics Letters, 2012)
A fundamental challenge in lithographic and microscopic techniques employing focused electron beams are so-called proximity effects due to unintended electron emission and scattering in the sample. Herein, we apply a method that allows for visualizing electron induced surface modifications on a SiN substrate covered with a thin native oxide layer by means of iron deposits. Conventional wisdom holds that by using thin membranes proximity effects can be effectively reduced. We demonstrate that, contrary to the expectation, these can be indeed larger on a 200 nm SiN-membrane than on the respective bulk substrate due to charging effects. © 2012 American Institute of Physics.

Magnetotransport properties of iron microwires fabricated by focused electron beam induced autocatalytic growth - Porrati, F.; Sachser, R.; Walz, Marie-Madeleine; Vollnhals, Florian; Steinrück, Hans-Peter; Marbach, Hubertus; Huth, M. (Journal of Physics D-Applied Physics, 2011)
We have prepared iron microwires in a combination of focused electron beam induced deposition and autocatalytic growth from the iron pentacarbonyl, Fe(CO), precursor gas under ultra-high vacuum conditions. The electrical transport properties of the microwires were investigated and it was found that the temperature dependence of the longitudinal resistivity (ρ) shows a typical metallic behaviour with a room temperature value of about 88 νΩ cm. In order to investigate the magnetotransport properties we have measured the isothermal Hall-resistivities in the range between 4.2 and 260 K. From these measurements, positive values for the ordinary and the anomalous Hall coefficients were derived. The relation between anomalous Hall resistivity (ρ) and longitudinal resistivity is quadratic, , revealing an intrinsic origin of the anomalous Hall effect. Finally, at low temperature in the transversal geometry a negative magnetoresistance of about 0.2% was measured. © 2011 IOP Publishing Ltd.

Surface-confined two-step synthesis of the complex (ammine)(meso- tetraphenylporphyrinato)-zinc(II) on Ag(111) - Flechtner, Ken; Kretschmann, Andreas; Bradshaw, Liam R.; Walz, Marie-Madeleine; Steinrück, Hans-Peter; Gottfried, Michael (Journal of Physical Chemistry C, 2007)
We report the first example of a surface-confined two-step synthesis of axially coordinated metalloporphyrin complexes in an ultrahigh vacuum environment. Specifically, a monolayer of tetraphenylporphyrin on an Ag(111) surface was metalated with coadsorbed Zn atoms, and thereafter, NH ligands were attached to the metal centers. The surface reactions were monitored with X-ray photoelectron spectroscopy. The approach outlined in this work can be employed to produce and study adsorbates of various axially coordinated porphyrin complexes, including biologically relevant systems. © 2007 American Chemical Society.

Tetraphenylporphyrin picks up zinc atoms from a silver surface - Kretschmann, Andreas; Walz, Marie-Madeleine; Flechtner, Ken; Steinrück, Hans-Peter; Gottfried, Michael (Chemical Communications, 2007)
We demonstrate that adsorbed meso-tetraphenylporphyrin molecules can coordinate Zn atoms that are pre-deposited on an Ag(111) surface, forming a complex that is identical to directly deposited tetraphenylporphyrinato-zinc(ii) ; this reaction, which we studied with XPS, is the first example of an oxidative dissolution of a metal by a large organic ligand under ultrahigh vacuum conditions. © The Royal Society of Chemistry.
UnivIS-Import:2015-04-14:Pub.2007.nat.dchph.lpc2.tetrap

Thin membranes versus bulk substrates: Investigation of proximity effects in focused electron beam-induced processing - Walz, Marie-Madeleine; Vollnhals, Florian; Rietzler, Florian; Schirmer, Michael; Kunzmann, Andreas; Steinrück, Hans-Peter; Marbach, Hubertus (Journal of Physics D-Applied Physics, 2012)
The resolution of focused electron beam induced processing techniques is limited by electron scattering processes. General wisdom holds that using a membrane, this can be effectively improved due to a cutoff of the electron interaction volume and thus diminished proximity effects. Recently, we demonstrated that in contrast to the expectation, proximity effects can be indeed larger on a 200nm silicon nitride membrane than on the respective bulk substrate, due to charging-induced surface activation. Herein, we expand these investigations on proximity effects in electron beam-induced surface activation to other substrates and to electron beam-induced deposition followed by autocatalytic growth. © 2012 IOP Publishing Ltd.